INSTRUMEN PENILAIAN PEMBELAJARAN AFEKTIF DI SEKOLAH DASAR - Nuruliana, Chandra; Tahfidzi, Nufus; Nugraha, Enung; Kultsum, Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning assessment does not solely focus on the cognitive domain but also includes the affective domain, which relates to students’ attitudes, values, and character development. This article aims to explore the concept of affective learning outcomes, the various affective domains according to Krathwohl’s Taxonomy, relevant operational verbs, and several assessment instruments such as Likert, Thurstone, Guttman, semantic differential, and rating scales. This study employs a descriptive approach using library research by analyzing various academic references. The results indicate that affective assessment plays a crucial role in shaping students’ personality and character. The appropriate use of assessment instruments enables educators to evaluate students’ attitudes and behaviors more objectively, systematically, and comprehensively. Therefore, affective assessment functions not only as an evaluation tool but also as a means of character formation based on moral and spiritual values.